The Extent of Social Responsibility among Libyan and Palestinian Telecom Companies in Mitigating the Effects of the COVID-19 Pandemic - Rashwan, Abdelrahman; Amarif, Suad (Jordan Journal of Applied Science-Humanities Series, 2024)
This study primarily aims to identify the social responsibility of Libyan and Palestinian telecommunications companies and their contributions to addressing the negative effects resulting from COVID-19. The study focuses on the companies’ efforts to alleviate the burden on the state and citizens, exploring the most significant social contributions made by these companies in response to the pandemic. To answer the research questions and test the hypotheses, the researchers employed a descriptive and analytical approach. After obtaining the necessary data, a validated and evaluated questionnaire was distributed to a sample of 53 individuals, including financial managers, internal auditors, financial analysts, and accountants working in Libyan and Palestinian telecommunications companies. The results of the study indicated that Libyan telecom companies did not contribute significantly to mitigating the negative effects of COVID-19 by activating their social responsibility roles. This conclusion is supported by the respondents' answers, which reflected a moderate degree of contribution, with a mean value of 3.08 and a relative weight of 61.69%, along with a standard deviation of 0.85 and a significance level (Sig) of 0.686. Similarly, Palestinian telecom companies also did not significantly contribute to mitigating the negative effects of the COVID-19 pandemic through their social responsibility roles. Respondents’ answers indicated a moderate level of contribution, with a mean value of 3.24, a relative weight of 64.85%, a standard deviation of 0.849, and a significance level (Sig) of 0.256. The study recommends that Libyan and Palestinian telecommunications companies should enhance their social roles in mitigating the negative effects of the COVID-19 pandemic by actively implementing social responsibility initiatives.
Keywords: COVID-19 Pandemic; CSR; Corporate Communications; Corporate Social Responsibility; Libya; Telecom Company